Preoperative albendazole treatment for liver hydatid disease decreases the viability of the cyst - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 1996)
Objective: Although in experimental models the efficacy of albendazole has been demonstrated, more clinical data are required. In this study, the effect of preoperative albendazole treatment was investigated in patients with liver hydatid cysts. Design: This is a prospective non-randomized study. Methods: In this study, the viability was assessed by the gross appearance of the cyst and intracystic pressure (ICP). The study consisted of 70 patients with 89 liver hydatid cysts in two groups. The patients in the first group (n=29) received 10 mg/kg albendazole orally for 3 weeks before surgery. Thirty-five cysts were evaluated in this group. The second group (n=41) with 54 liver hydatid cysts received no preoperative treatment. Results: In the first group receiving preoperative albendazole, 20 cysts were viable and 15 non-viable. The median ICP was 21 (range 8-56) cm H2O in viable and 0 (range 0-8) cm H2O in non-viable cysts. In the second group, 43 cysts were viable and 11 non-viable. The median ICP was 35 (range 8-75) cm H2O in viable and 0 (range 0-2) cm H2O in non-viable cysts. The ICP values of viable cysts in the first group receiving preoperative albendazole were significantly lower (P<0.05). The number of non-viable cysts was also significantly higher in the group treated with preoperative albendazole (P<0.05). Conclusion: Albendazole in this study has proved to be effective in decreasing the viability of liver hydatid cysts when given for 3 weeks preoperatively.
Keywords: albendazole; hydatid disease; liver; surgery; EXPERIMENTAL PERITONEAL HYDATIDOSIS; CHEMOTHERAPY